2006
DOI: 10.1103/physrevlett.96.122501
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Nuclear Isovector Valence-Shell Excitations

Abstract: Excited states in 138Ce have been studied via the 12C(138Ce, 138Ce*) Coulomb excitation reaction at 480 MeV. Relative cross sections have been determined from the gamma-ray yields observed with Gammasphere. The E2 and M1 strength distributions between the lowest six 2+ states up to 2.7 MeV enables us to identify the 2(4)+ state in 138Ce as the dominant fragment of the one-phonon 2(1,ms)+ mixed-symmetry state. Mixing between this level and a nearby isoscalar state is observed and is more than 4 times larger tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 25 publications
5
92
0
Order By: Relevance
“…These absolute E2 transition strengths test the validity of the selection rules directly; in the cases of O(6) and O(5) symmetries, E2 transitions are allowed between states with ∆σ = 0 and ∆τ = ±1. This experimental information is rarely available, but it has been shown [14,15,17] that projectile Coulomb excitation can serve as a powerful tool to obtain it. The purpose of the present study is to investigate the 126 Xe low-spin states with projectile Coulomb excitation.…”
mentioning
confidence: 99%
“…These absolute E2 transition strengths test the validity of the selection rules directly; in the cases of O(6) and O(5) symmetries, E2 transitions are allowed between states with ∆σ = 0 and ∆τ = ±1. This experimental information is rarely available, but it has been shown [14,15,17] that projectile Coulomb excitation can serve as a powerful tool to obtain it. The purpose of the present study is to investigate the 126 Xe low-spin states with projectile Coulomb excitation.…”
mentioning
confidence: 99%
“…In contrast to the single isolated one-phonon 2 + 1,ms states of 132 Te [5], 134 Xe [6], and 136 Ba [7], a fragmented 2 + 1,ms state was observed in 138 Ce [4]. This fragmentation was ascribed to a lack of shell stabilization [4], a hypothesis that was supported in microscopic calculations [8]. It was concluded that the observed fragmentation is a shell effect caused by the specific subshell structure and pairing correlations.…”
Section: Published By the American Physical Society Under The Terms Omentioning
confidence: 85%
“…4; for details see [9]). It exhibits [4,5,9,[20][21][22]. The value for 140 Nd [9] was determined in another experiment in the same experimental campaign.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two domains reveal different behavior of mixed-symmetry excitations. The mixed-symmetry properties are concentrated predominantly in a single state [6,7] of 94 Mo while around N = 82 there is fragmentation of mixed-symmetry strength [8][9][10].…”
Section: Introductionmentioning
confidence: 99%